Purple sandpipers (Calidris maritima) feeding in an Arctic estuary: tidal cycle and seasonal dynamics in abundance - Regelin, Beke (Uppsala universitet, Institutionen för biologisk grundutbildning, 2011)
The purple sandpipers (Calidris maritima) are the most common waders in the high arctic archipelago of Svalbard, Norway. There they have to cope with a very short summer season and high metabolic costs of migrating far north and breeding in an arctic environment. The food on land is usually scarce, whereas there are rich feeding grounds in the littoral zone, such as in the intertidal zone of river flats. These feeding grounds are though only available to the purple sandpipers during low tide and as long as the estuary is not covered by sea ice. One of these intertidal flats was used as the fieldwork area in this study. To study when the birds are coming to this intertidal flat for feeding, a count study was performed during the entire stay of the purple sandpipers in Svalbard in summer 2010. Point counts were performed at low tide during 118 different days. Additionally, point counts were performed at twenty days during the six hours of the entire low tide period, to study when during the tidal cycle most sandpipers were feeding at the estuary. Most sandpipers were counted at the intertidal flat at the beginning of June with the highest number, 921 individuals, on 8th June. When the tundra was free of snow and the birds could start breeding, numbers where rapidly declining with very few sandpipers left in the estuary in July and the first part of August. From the end of August numbers were increasing again with a second but lower peak in the end of September and beginning of October. By the end of October all sandpipers had left the estuary. The study on the appearance of purple sandpipers at the estuary at the different periods of low tide showed that there were significantly more sandpipers between low tide and half an hour later than at the rest of the low tide period. This might be due to better access to their prey at that time. This knowledge could be used in future studies aiming at recording the maximum numbers. The result of the phenologic study could be included in a long term monitoring to see if the ...